2020
DOI: 10.1002/wea.3854
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of a Mt Everest snowstorm from the world's highest surface‐based radar observations

Abstract: Sherpa SF, Wagnon P, Brun F et al. 2017. Contrasted surface mass balances of debris-free glaciers observed between the southern and inner parts of the Everest region (2007-15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The presence of a deep moist layer extending above 8,000 m asl appears to be an important factor in the formation and persistence of heavy precipitation and is consistent with vertically pointing radar observations from Everest Base Camp during a pre-monsoon snowstorm that indicated highest radar reflectivity occurring in association with higher echo top heights. 87 Shallower lapse rates during heavy precipitation are more likely a product of latent heat release associated with higher moisture content. 76 Despite CMIP5 model projections of increased precipitation in the upper reaches of the Koshi basin, 61 the strongly negative mass balance in glacier ablation zones associated with rising freezing levels, and likely compounded by the increased latent heat release and higher specific humidity, is almost certain to counteract any positive mass balance from increasing snowfall in accumulation zones.…”
Section: Articlementioning
confidence: 99%
“…The presence of a deep moist layer extending above 8,000 m asl appears to be an important factor in the formation and persistence of heavy precipitation and is consistent with vertically pointing radar observations from Everest Base Camp during a pre-monsoon snowstorm that indicated highest radar reflectivity occurring in association with higher echo top heights. 87 Shallower lapse rates during heavy precipitation are more likely a product of latent heat release associated with higher moisture content. 76 Despite CMIP5 model projections of increased precipitation in the upper reaches of the Koshi basin, 61 the strongly negative mass balance in glacier ablation zones associated with rising freezing levels, and likely compounded by the increased latent heat release and higher specific humidity, is almost certain to counteract any positive mass balance from increasing snowfall in accumulation zones.…”
Section: Articlementioning
confidence: 99%
“…We build off the above to make a conservative estimate of the mean air temperature at Mt Everest's unmonitored summit, taking the mean air temperature at the South Col during the monsoon (where winds are faster and solar heating of the temperature sensor is less likely), and then integrating the SALR (1) to 8849m. We assume that the SALR remains appropriate up to the summit because Perry et al (2020) observed precipitation echo tops extending to almost 10 000m above sea level during a snowstorm on Mt Everest in May 2019.…”
mentioning
confidence: 99%
“…(1) and then integrating the SALR to 8849m. We assume that the SALR remains appropriate up to the summit because Perry et al (2020) observed precipitation echo tops extending to almost 10 000m above sea level during a snowstorm on Mt Everest in May 2019.…”
mentioning
confidence: 99%
“…Thus, five meteorological stations established by National Geographic Society and Rolex Perpetual Planet Expedition around Everest expedition route, up to 8400 meter, presents us with unique opportunity to not just update and extend previous studies (Mathews et al 2020, Shea et al, 2015 but also to validate the models (Dawadi et al, 2021) and understand the critical role driven by meteorology for glacial evolution. Several studies has been conducted using Everest station (Grey et al, 2022;Khadka et al, 2021;Matthews et al, 2020;Matthews et al, 2022;Perry et al, 2020;Perry et al, 2021) , however detail analysis of meteorological variables covering all season of the year and its diurnal cycle has not been done yet. Thus, this study aims to presents a detail meteorological analysis using some of the world's highest AWSs.…”
Section: Introductionmentioning
confidence: 99%